Principles and Legal Basis for Constitutional Court Procedure - Ifansyah Rizki, Ifansyah Rizki; Arif Wibowo (JUSTICES: Journal of Law, 2025)
Principles and legal basis are the most important components of law to be used as benchmarks for judges and other judicial institutions when handling a case in court. Just like other procedural law, the procedural law of the constitutional court also has principles and also a legal basis which is used as a reference when proceeding at trial in handling a case. These principles and legal bases must always be upheld by the judge so that the decisions issued are not wrong or correct so as to avoid decisions that deviate from the provisions of the procedural law of the constitutional court. With the principle and legal basis for the procedural law of the constitutional court, it aims to become a guideline or benchmark or principle that must be applied and become the supremacy of the constitution and become a protection for people who have constitutional rights. If these principles are carried out as well as possible by the judge and his staff, then justice and constitutional rights will work properly.